2019
DOI: 10.32493/skt.v3i1.3270
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas ,Ukuran Perusahaan Terhadap Leverage Implikasi Terhadap Nilai Perusahaan Cosmetics and Household yang terdaftar di Bursa Efek Indonesia

Abstract: Tujuan dari penelitian secara empiris untuk membuktikan adanya Pengaruh Profitabilitas ,Ukuran Perusahaan Terhadap Leverage Implikasi Terhadap Nilai Perusahaan Cosmetics and Household yang terdaftar di Bursa Efek Indonesia baik secara parsial maupun simultan. Peneliti menggunakan sampel 5 emiten dengan kapitalisasi pasar terbesar dari Index Saham LQ45 Bursa Efek Indonesia. mulai tahun 2011-2017. Penelitian menggunakan sampel 5 perusahaan cosmetics and household yang diambil dengan menggunakan teknik purposive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
5
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 1 publication
1
8
5
11
Order By: Relevance
“…Research on profitability has had mixed results. First, previous research found that profitability has a positive effect on firm value (Noviani et al, 2019;Rudangga & Sudiarta, 2016;Kadim & Sunardi, 2019). The results of this study contradict research from Ratih & Damayanthi (2016) who found that profitability cannot affect firm value.…”
Section: Introductioncontrasting
confidence: 83%
“…Research on profitability has had mixed results. First, previous research found that profitability has a positive effect on firm value (Noviani et al, 2019;Rudangga & Sudiarta, 2016;Kadim & Sunardi, 2019). The results of this study contradict research from Ratih & Damayanthi (2016) who found that profitability cannot affect firm value.…”
Section: Introductioncontrasting
confidence: 83%
“…Leverage (debt to equity ratio) does not influence company stock value (price to book value). This result, therefore, does not support prediction of H1 stating that leverage has a negative influence on company stock value but, on the other hand, supports results of the study conducted by Kadim and Sunardi (2019). Nevertheless, despite being not significant, the influence of leverage on stock value is found to be negative.…”
Section: Discussion the Influence Of Leverage On Company Stock Valuecontrasting
confidence: 93%
“…Results of the study conducted by Kadim and Sunardi (2019) indicated that debt to equity ration negatively influenced company's stock price; meanwhile, Ginting and Suriany (2013) discovered that the use of leverage in capital structure negatively influenced value of the company. This results have been opposed to cost of capital theory stating that debt is low cost external financing that will increase value of the company.…”
Section: Leverage and Its Influence On Stock Valuementioning
confidence: 99%
See 2 more Smart Citations